Socioeconomic profile of family farmers in the municipality of Muniz Freire, Espírito Santo - Madeira Álvares da Silva Conforti, Adriana; Jorden Almança, Carlos Cesar; Miranda Barbosa, Wagner; Oliveira dos Reis, Schalana; Dalbó, Juliana; Vitorino Freitas, Flávia; Oliveira Mendes, Suzanny; Gasparini dos Santos, Joaquim; Madeira da Silva Guanaes, Gabriel; Assis Robe, Gabrielly; Vidal Monteiro da Silva Couto, Cinthia; Ribeiro Borçoi, Aline; et al. (Guará Journal, 2016)
Although the national importance of family farming and targeted government policies, socio-economic conditions of this population are little known. The aim of the study was to outline the socio-economic profile of farmers in the municipality of Muniz Freire, ES. They interviewed 82 farmers on the spot. Descriptive statistics for data analysis was used. According to results, the age of respondents was 20-81 years. Among the evaluated, 76.83% reported having children. The use of tobacco has been reported by 9.76%. Most had not completed elementary school. When asked about skin color, it was observed predominance of response to white. Most farmers owned the land and the lack of access to sanitation and garbage collection systems was observed. Work on the plantation as exclusive activity was reported by the majority. Analysis of the monthly family income of farmers showed that the pay was low. Based on these results, it concluded a first data collection in the region, which significantly contribute to the continuity of work, establishing future extension actions and promote improved health and well-being of the population studied.